Evaluating the Effectiveness of Enoxaparin in Treating Pediatric Arterial Thrombosis in Saudi Arabia - Meshary Al-Meshary; Abdulrahman Alotaibi; Nouf S. Alsagri; Asmaa AlZhrani; Husam I. Ardah; Mohammed A. Alnuhait (MDPI AG, 2024)
Background: Thrombosis is the abnormal formation of blood clots within blood vessels; it results from an imbalance between fibrinolytic, pro-coagulant, and anticoagulant systems. Pediatric arterial thrombosis, especially related to catheter usage, is an emerging issue with limited evidence. This study evaluates the efficacy of enoxaparin in treating arterial thrombosis in pediatric patients at a single center. Methods: A retrospective single-center study included children under 14 years old diagnosed with catheter-related arterial thrombosis (CAT) and treated with low-molecular-weight heparin (LMWH) at King Abdulaziz Medical City between 2016 and 2021. Patients without follow-up at our institution or those using other anticoagulants were excluded. Data collected included age, sex, weight, catheter type, location and degree of thrombosis, ultrasonographic results, treatment duration, hemoglobin and platelet levels, and missed refills. Radiologic confirmation of CAT was required for inclusion. Results: This study included 111 children treated with enoxaparin for non-cerebral arterial thrombosis. The median age at diagnosis was 3 months, with 58% being male patients. Most cases (87%) involved cardiac catheterization, and all were confirmed using ultrasonography. Complete thrombus resolution was achieved in 90% of patients, partial resolution in 8.1%, and 1.8% had no resolution. The median duration of enoxaparin therapy was 20 days. Multivariate analysis indicated that higher age and lower body weight were associated with a higher risk of non-resolution. Indwelling catheters also posed a greater risk of non-resolution compared to cardiac catheters. Conclusions: Enoxaparin proved effective in treating catheter-related arterial thrombosis in children, with high resolution rates and few side effects. This study helps inform treatment strategies in pediatric thrombosis management and highlights the need for further research to refine treatment durations and address patient risk factors.